2019
DOI: 10.1016/j.jsps.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydroxylated solvents on the active constituents of Salvadora persica root “Siwak”

Abstract: Previously, the antimicrobial activity of Salvadora persica was traced to benzyl isothiocyanate. In the present study known inactive compounds were isolated from extracts obtained by different solvents including β-amyrin, β-sitosterol, stigmasterol glucoside, benzyl cyanide and sulphur. However, some inactive compounds were present only in the ethanol and methanol extracts. This observation indicated that these compounds most likely are artifacts resulted from interaction with the solvents used in extraction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…These reactions proceed at room temperature and accelerated by heating. The study also indicated that chloroform and acetone did not express any effect on benzyl isothiocyanate (Abdel-Kader et al, 2019). In the current study we focused on the effect of extraction conditions and samples preparation.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…These reactions proceed at room temperature and accelerated by heating. The study also indicated that chloroform and acetone did not express any effect on benzyl isothiocyanate (Abdel-Kader et al, 2019). In the current study we focused on the effect of extraction conditions and samples preparation.…”
Section: Resultsmentioning
confidence: 89%
“…The effect of solvents revealed that chloroform gave the highest yield of benzyl isothiocyanate followed by acetone and finally ethanol. As a hydroxylated solvent ethanol expected to react with benzyl isothiocyanate leading to very low yield (Abdel-Kader et al, 2019). The loss due to the use of ethanol is great when compared with chloroform under all the used condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ( Abdel-Kader et al, 2019a ) have examined hydroxylated solvents’ effect on the active components of S. persica root. They found that only solvents with hydroxyl groups reacted with benzyl isothiocyanate and gave products similar to those isolated from the alcohol extracts.…”
Section: Analytical Standardization Methodsmentioning
confidence: 99%
“…Other pharmacological properties reported for S. persica include hypolipidemic, antiulcer, anticonvulsant, antimycotic, antidepressant, and analgesic ( Sabbagh et al, 2020 ). The plant is known to contain active ingredients such as oleic acid, salvadourea, salvadorine, linoleic acid, trimethylamine, lignans, etc ( Abdel-Kader et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%